GEOMORPHOLOGY AND ITS DIFFERENT PARAMETERS IN THE FLOOD PRONE LOWER GANDAK PAIN - Ramashray Prasad; Jitendra Rishideo (Zenodo, 2021)
The physical appearance of any area is the outcome of geomorphological interactions between endogenic and exogenic processes. Endogenic processes are very slow while the exogenic are quite obviously observable operating at or from above the surface of the area. They may be included like - wind, fluvial, glacio-fluvial, glacier, permafrost, karst etc. They sculpture the concerned area and people use the same for their own needs. Land use may be seen in two ways - natural or human induced use of land. The Lower Gandak Plain is characterized by flooding in the monsoon period when torrential rain associated with glacier melt water occupy the low lying area in the region. But this huge amount of water is brought by numerous tributaries of Gandak from upper Himalayan catchment. Therefore, enormous water from Himalayan catchment is to be drained through the Lower Gandak Plain. The Gandak flood plain is highly populated and anthropogenic activities are prominent. So, most of the areas have human sign and less as natural. Flooding is, therefore, more due to anthropogenic factors. Hence, an attempt has been made here to (i) evaluate the geomorphological characteristics, (ii) elaborate the flood plain forming processes on the basis of planforms, and (iii) explain various geomorphological parameters in the Lower Gandak Plain. This study is expected to help in systematic and integrated plan preparation for overall development of the Lower Gandak Plain on the basis of detail characteristics of the area explained.